Phenomenology as performative exercise - Guidi, Lucilla,; Thomas, Rentsch, (Studies in Contemporary Phenomenology;, 2020)
"This volume, edited by Lucilla Guidi and Thomas Rentsch, establishes the first systematic connection between phenomenology and performativity. On the one hand, it outlines the performativity of phenomenology by exploring its enactment and the transformation of attitude it effects; this exploration is conducted through a number of parallels between phenomenology and the ancient understanding of philosophy as an exercise and a way of life. On the other hand, the volume examines different notions of performativity from a phenomenological perspective, so as to show that a phenomenological understanding of embodied experience complements a linguistic account of performativity and can also offer a ground for bodily practices of resistance, critique, and self-transformation in our own day and age".